2004
DOI: 10.1097/00042752-200407000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Affects Proliferation and Collagen Synthesis by Human Patellar Tendon Fibroblasts

Abstract: Based on these in vitro findings, we speculate that production of prostaglandin E2 in tendons might play some role in the acellularity and matrix disorganization seen in exercise-induced tendinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 23 publications
7
68
0
1
Order By: Relevance
“…This study also showed that PGE 2 at 100 ng/ml significantly decreased HPTF proliferation, which is consistent with the result of our previous report (Cilli et al, 2004). Furthermore, low concentrations (≤1 nM) of LTB 4 negated the inhibitory effect of PGE 2 on HPTF proliferation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study also showed that PGE 2 at 100 ng/ml significantly decreased HPTF proliferation, which is consistent with the result of our previous report (Cilli et al, 2004). Furthermore, low concentrations (≤1 nM) of LTB 4 negated the inhibitory effect of PGE 2 on HPTF proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…6). These results suggest that PGE 2 -mediated inhibition of collagen production, as shown in our previous study (Cilli et al, 2004), is perhaps via the induction of collagen-degrading enzymes such as MMP-1 and MMP-3. Another possibility for the decrease in collagen production by PGE 2 is that PGE 2 affects collagen mRNA stability.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results of the increased levels of VEGF in tendons are mainly two: on the one hand the alteration of the tendon matrix which leads to a weakening of the tendon structure; on the other hand the following nervous ingrowth that causes pain symptoms. It was recently shown that human tendon increase in proliferation (as well as gene expression and type I collagen production) in a stretching magnitude-dependent manner [112] ; overload, on the opposite, can decrease proliferation and collagen production in human tendon fibroblasts, changing the extracellular matrix composition and even resulting in tenocytes apoptosis (programmed cell death) [113][114][115] . Since tenocytes are required to maintain homeostasis of the extracellular matrix (ECM) by regulating the balance between its synthesis and degradation [116] , tenocyte apoptosis may compromise the ability of the tendon to regulate repair processes.…”
Section: The Plantaris Longus Tendon and Its Relationship With The Acmentioning
confidence: 99%